The role of social resources in securing life and livelihood in rural Afghanistan - Paula Kantor; Adam Pain (University of Bath, Centre for Development Studies (CDS), 2011)
This paper examines how rural Afghan households in five villages located in Badakhshan and Kandahar provinces have negotiated within contexts of weak formal institutions and localized power to achieve physical and economic security. The paper uses household case studies to assess how the concepts of informal security regimes and dependent security aid understanding of the means through which rural households in Afghanistan seek security. It particularly examines how different households' are integrated into social relationships, the variable quality and usefulness of these relationships, and under what conditions they might facilitate autonomous versus dependent security. In doing so the paper explores the importance of context, linking the details of household experiences to their village and provincial locations. It provides an understanding of opportunities for and constraints to rural transformation in Afghanistan based on the social hierarchies and relations present, illustrating the complexities with which interventions aimed at improving human security and reducing poverty must engage, interventions which to date have focused more on filling gaps in access to human and material resources than on addressing the root causes of poverty.
Keywords: 330; Öffentliche Sicherheit; Entwicklungshilfe; Sozialkapital; Soziale Lage; Afghanistan